Expression Analysis of Cytokine and Chemokine Genes during the Natural Course of Murine Experimental Autoimmune Uveoretinitis. (20th September 2012) - Hashida, Noriyasu; Ohguro, Nobuyuki; Nishida, Kohji
Abstract : C57BL/6 mice were immunized with human interphotoreceptor retinoid-binding protein peptides to induce experimental autoimmune uveoretinitis (EAU). From the day of immunization to 30 days later, RNA was isolated daily from the mouse eyes. Dynamic changes in gene expression during the pathogenesis of EAU were analyzed by TaqMan gene expression assay that contained most chemokines/cytokines and their receptors, and signal transducer and activator of transcription ( STAT ) family genes, using beta-actin as the endogenous control. Gene clusters based on their expression profiles were analyzed to determine the candidate genes for the pathogenesis of inflammation. Hierarchical cluster analysis showed gene expression during EAU development in seven clustering patterns. Hierarchical cluster analysis also identified four distinct phases in daily expression: entrance, acceleration, deceleration, and remission. Gene expression changes in the EAU active phase showed synergetic upregulation of Th1 -type genes (IFN-gamma and CXCL10/IP-10 ) with elevated Th2 -type genes ( CCL17/TARC and IL-5 ). Sequential expression changes of STAT1, STAT6, and STAT3 genes represented the dynamic changes of Th1, Th2, and Th17 -type inflammatory genes, respectively. The expression pattern of STAT1 was representative of many gene movements. Our results suggested that coordinated action of Th1, Th2, and Th17 genes and STAT family genes are involved in EAU development and resolution.